The Effect of Banning Fireworks on Air Quality in a Heavily Polluted City in Northern China During Chinese Spring Festival - Liu, Dexin; Li, Wanlong; Peng, Jianbiao; Ma, Qingxia (Frontiers in Environmental Science, 2022)
Air pollution has a negative impact on the ecological environment as well as on the health of people. Setting off fireworks and firecrackers lead to a significant deterioration in air quality in a short period of time. The firework prohibition policy of 2016 in Zhengzhou City provides an opportunity to investigate the effect of banning fireworks on air quality during the Spring Festival. The Air Quality Index and the concentrations of PM2.5, PM10, SO2, NO2, CO and O3 during the Spring Festival between 2014 and 2019 in Zhengzhou City were analyzed. The results show that: There were small fluctuations in precipitation, air pressure, wind speed, temperature and relative humidity during the Spring Festival from 2014 to 2019. The air quality index in the Spring Festival in 2016 was significantly lower than that in 2014 and 2015, and the air quality in 2018 and 2019 showed greater improvements. The sudden increases in pollutants concentrations has been weakened, showing an obvious “peak-shaving” effect during the traditional heavy pollution period, New Year’s Eve to the first day of the first lunar month. In 2014 and 2015 years, the concentrations of PM2.5 and PM10 reached their peaks at 1:00 a.m. on the first day of the new year, and fluctuated in the ranges of 259–271 μg/m³ and 380–384 μg/m³, respectively. The concentrations of PM2.5 and PM10 were 44 and 100 μg/m³, respectively in 2016, 40 and 80 μg/m³ in 2018 during the same period. In addition, the ban implemented has the most obvious impact on PM2.5 and PM10. Compared with the Spring Festival in 2014, the concentrations of PM2.5 and PM10 increased by 19.15 and 18.64% in 2015, decreased by 18.38% and 15.90% in 2016, and decreased by 16.83% and 26.05% in 2018. Therefore, banning fireworks and firecrackers will help to improve the air quality during the Spring Festival in Zhengzhou City to a certain extent.